2014
DOI: 10.1111/jan.12513
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of fentanyl in the pre‐emptive treatment of pain associated with turning in patients under mechanical ventilation: research protocol

Abstract: If pre-emptive fentanyl is more effective than placebo and reasonably safe, the results of the current study may change nursing attitude in managing turning in critically ill patients. As a consequence, pain may be decreased during this nursing procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…The sensor sends different signals, including the BIS index score, EMG activity, and electroencephalographic data (EEG). The range of BIS values is from 0 (complete suppression of EEG or coma) to 100 (fully awake) (13). …”
Section: Methodsmentioning
confidence: 99%
“…The sensor sends different signals, including the BIS index score, EMG activity, and electroencephalographic data (EEG). The range of BIS values is from 0 (complete suppression of EEG or coma) to 100 (fully awake) (13). …”
Section: Methodsmentioning
confidence: 99%
“…Studies published to date show that pain continues to be a problem in intensive care units (ICUs) despite progress in pain research and management in the last 20 years 1,2,3 . The rates of uncontrolled pain in critically ill patients remain unacceptably high 2,4,5 . More than 50% of critically ill patients experience pain during their stay in ICU 1,4,6 .…”
mentioning
confidence: 99%
“…The stimulus we chose was the turning of the patient for washstand. Previous studies showed that patient turning was one of the most painful nursing procedures [ 21 ]. Each patient was his own control, and could only be included once in the study.…”
Section: Methodsmentioning
confidence: 99%